Filtered cathodic vacuum Arc deposition of nano-layered composite coatings for machining hard-to-cut materials. Issue 5 (May 2016) - Volkhonskii, A.; Vereshchaka, A.; Blinkov, I.; Vereshchaka, A.; Batako, A.
Abstract In coated tools, the grain boundaries and coating layers are areas of intense energy dissipation, which hardens the coating material by increasing its toughness and its resistance to the formation and development of cracks. An increase in the efficiency of the coatings was achieved by applying nano-dispersed multilayer composite structure. This paper proposes using nano-scale multilayer composite coating based onTiN-CrN compound to improve thermal stability, where barrier layers based onZrNbN have been introduced. TheZrNbN barrier does not interact withTiN andCrN at temperatures around 1000 °C. The influence of process parameters of the filtered cathodic vacuum arc deposition on the composition, structure and properties of the coatings based on variation ofTiAlN-ZrNbN-CrN was analysed. The results presented here show that the hardness of the developed coatings was as high as 38 GPa. Subsequently, the carbide tools used in this study with the new coatings had an increased lifetime of 1.5–2.0 times compared to tools with commercial coatings. The coated carbide tools were tested in longitudinal turning and face milling titanium and nickel alloys.